Nilai pH dan deteksi Salmonella sp. Daging sapi di pasar tradisional dan pasar modern di wilayah surabaya timur - Sheila Marty Yanestria; Asih Rahayu; Atina Atina (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2021)
The purpose of this study was to determine the pH value and detection of Salmonella sp beef in traditional markets and modern markets in East Surabaya. This type of observational research with descriptive analysis based on the range of normal pH values ​​of beef and the biochemical properties of Salmonella sp. The samples used consisted of the following: traditional markets with codes A, B, C, D, and E, and modern markets with codes 1, 2, 3, 4, and 5. Each sample taken from each market consisted of cooked meat. deep or tenderloin with 2 different pieces. Based on the results of the study showed that there was no significant difference in the pH value of beef from traditional markets and modern markets in East Surabaya (P <0.05) and there was 1 positive meat sample for Salmonella sp from traditional markets and 2 meat samples. Positive Salmonella sp which comes from the modern market.